Pierre Bourdieu al español: a propósito de la circulación de bienes simbólicos - Dimas Marquez, Sandra Saraí (2026)
Classical social theory has been produced mainly in Francophone, Germanic, and Anglophone contexts, which makes translation an indispensable element not only for access to knowledge but also as a mechanism of intellectual consecration and circulation of symbolic goods within the international academic field. The aim of this article is to analyze the translation of Pierre Bourdieu’s work into Spanish as a process of symbolic circulation involving operations of selection, marking, and interpretation, articulated with the dynamics of production, circulation, and consumption. Methodologically, the study is based on a documentary analysis of a corpus of translated works published between 1958 and 2024. The results highlight the central role of editorial mediation, translators, and the timing of translations in the appropriation and fragmentation of Bourdieu’s thought. It is concluded that reading Bourdieu in translation entails engaging with his work through mediators and legitimizing devices that shape its reception.